2020
DOI: 10.5713/ajas.19.0388
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lonicera japonica extract on performance, blood biomarkers of inflammation and oxidative stress during perinatal period in dairy cows

Abstract: Objective: An experiment was conducted to evaluate the effects of Lonicera japonica extract (LJE) on milk production, rumen fermentation and blood biomarkers of energy metabolism, inflammation and oxidative stress during the perinatal period of Holstein dairy cows.Methods: Eighteen Holstein dairy cows were used in a complete randomized design experiment with 3 dietary treatments and 6 cows per treatment. All cows received the same basal total mixed ration (TMR) including a prepartal diet (1.35 Mcal of net ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…Table 2 summarized the application of L. japonica (extract) in animal production in recently years. It showed that these studies mainly focus on pigs ( Liu W. et al, 2016 ), beef cattle ( Fu et al, 2016 ; Yejun et al, 2019 ), dairy cows ( Ma et al, 2020a , b ; Zhao et al, 2020 ), broiler ( Müştak et al, 2015 ), laying hens ( Long et al, 2018 ), Penaeus monodon ( Chen et al, 2013 ), grass carp ( Meng et al, 2019 ), and olive flounder ( Dharaneedharan et al, 2016 ).…”
Section: Application Of L Japonica In Animal Productionmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 2 summarized the application of L. japonica (extract) in animal production in recently years. It showed that these studies mainly focus on pigs ( Liu W. et al, 2016 ), beef cattle ( Fu et al, 2016 ; Yejun et al, 2019 ), dairy cows ( Ma et al, 2020a , b ; Zhao et al, 2020 ), broiler ( Müştak et al, 2015 ), laying hens ( Long et al, 2018 ), Penaeus monodon ( Chen et al, 2013 ), grass carp ( Meng et al, 2019 ), and olive flounder ( Dharaneedharan et al, 2016 ).…”
Section: Application Of L Japonica In Animal Productionmentioning
confidence: 99%
“…Moreover, in vitro studies showed that L. japonica extract could regulate rumen fermentation and reduce methane production by inhibiting the growth of methanogenic bacteria ( Huang et al, 2019 ; Yejun et al, 2019 ). Studies on dairy cows showed that dietary supplementation of L. japonica extract could relieve heat stress of dairy cows by improving immune and antioxidant capacity ( Ma et al, 2020a , b ; Gao et al, 2021 ), enhancing anti-inflammatory activity ( Zhao et al, 2020 ). Meanwhile, L. japonica extract can improve rumen microbial diversity and improve rumen fermentation capacity ( Tang et al, 2018a ).…”
Section: Application Of L Japonica In Animal Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meng et al found that supplementing HE could reduce the mRNA expression of fat synthesis-related genes, strengthen the intestinal mucosal barrier of grass carp, improve lipid metabolism and immune function, and reshape the intestinal flora ( 9 , 10 ). Zhao et al found that supplementing HE during the perinatal period improved dry matter intake, lactation capacity, anti-inflammatory properties, and antioxidant capacity of dairy cows ( 11 ). Its effect on geese has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%